Optimalisasi Jumantik dan Pemberantasan Sarang Nyamuk dalam Mencegah Penularan Infeksi Virus Dengue pada Kader di Desa Karangbangun: Optimizing Human Resources and the Environment in Preventing the Transmission of Dengue Virus Infection to Cadres in Karangbangun Village - Bestari, Rochmadina Suci; Jatmiko, Safari Wahyu; Aisyah, Riandini; Wahyuni, Sri; Mahmudah, Nur; Agustina, Tri; Salsabila, Nabila Mutia; Adha, Muhammad; Kumala, Aswa Arsa; Fauzi, Favian Arriella Shabri Ikmal (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Dengue virus infection (IVD) is still a health problem in Indonesia. In Karangbangun Matesih Karanganyar Village, there were 13 cases of IVD in April 2024. The government program to eradicate IVD vectors has not been implemented optimally. Karangbangun Village has potential healthcare resources to be used as agents for eradicating IVD vectors. So far there has been no education about the function of jumantik as larva monitors and mosquito nest eradication (PSN). Therefore, it is necessary to provide education about the function of jumantik and PSN to health cadres in Karangbangun Village. The aim and benefit of this community service activity is that the health cadres of Karangbangun Matesih Karanganyar Village understand the function of jumantik and PSN. The extension activity was preceded by a pretest, and speaker presentation and ended with a posttest. The results of the education showed an increase in health cadres' knowledge after the education based on a comparison of pre-test and post-test scores (p<0.001; Effect Size (Cohen's d) = -1.993). Education about the function of jumantik and eradicating mosquito nests to health cadres in Karangbangun Village increased knowledge significantly and the average post-test score showed an increase.